Improving Student’s Achievement In Fiqh Subject By Using Audio Visual Of Class VII A Of MTS YPIP Panjengin - Muhammad Rasyidil Fikri Alhijri (Classroom: Journal of Islamic Education, 2025)
Audio visual learning media have a major influence in educational technology. This research aims to determine the improvement in students’ achievement in the materials of the VII-A MTs YPIP Panjeng by using audio visual learning media. This research employs Class Action Research (CAR) design using the model of Kurt Lewin consisting of 2 cycles and using 4 stages: planning, implementation, observation, and reflection. The data collection techniques used in this research aretests, observation, interviews, and documentation. The results showed that there was an increase in students’ achievement on Fiqh subject of the Jama and Qashar materials at Cycle I and prayers are in emergency during the Cycle II. This is based on the results of Cycle I which have an average value of students’ achievement of 85.95 with a student's submission of 78% or as many as 22 of 30 students and students’ enthusiasm of 63% with the category (good). In Cycle II has a median value of students’ achievement of 93,73 with students submission of 100% or as many as 30 students and students’ enthusiasm at 78% with the category (excellent).